As especificidades da tradução de literatura infantojuvenil: análise de três traduções de Voyage au Centre de La Terre (Viagem ao Centro da Terra), de Jules Verne - Rando, Fernanda Silva [UNESP] (2014)
The translator of children's literature deals with the same issues as the translator of adult literature, i.e., the historical, social and cultural context in which both the source text and the translated text are inserted. However, he has to pay attention to the fact that children's literature is of an asymmetrical character, i.e., that it is written, translated, edited, and purchased by adults for non-adults. Therefore, the translation of children's literature is strongly influenced by the image the translator has of its target public. Our research took into account three different translations of the classic Journey to the Center of the Earth, by Jules Verne, to address the possible issues involved in the translation of children's literature. A comparative analysis of the translations was conducted to achieve our specific research goal, which was to find out if the fact that it is a book for children and adolescents influenced the translations regarding the ethics of equality, i.e., if they assimilate the foreign text to the target culture and/or perform reduction operations by eliminating sentences or words and by using generic terms instead of specific ones. We first took into account the paratextual and epitextual elements of each translation and then compared extracts that presented discrepancies, according to the terminology by Venuti (1995a). The analysis of the extracts aimed to identify the strategies used by the translators in order to tackle issues regarding the description of characters and places, cultural and historical references (such as names, food, habits, etc.), technical terms, and foreignisms. Our theoretical reference was based on the concepts of domestication and foreignization (VENUTI, 1995a and 2002) and on the ethics of translation (BERMAN, 1995 and 2013; VENUTI, 2002; OLIVEIRA, 2005, 2006, 2007 and 2008). The comparison of the extracts showed different ...